2003
DOI: 10.1289/ehp.6064
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose exposure to inorganic mercury accelerates disease and mortality in acquired murine lupus.

Abstract: Inorganic mercury (iHg) is known to induce autoimmune disease in susceptible rodent strains. Additionally, in inbred strains of mice prone to autoimmune disease, iHg can accelerate and exacerbate disease manifestations. Despite these well-known links between iHg and autoimmunity in animal models, no association between iHg alone and autoimmune disease in humans has been documented. However, it is possible that low-level iHg exposure can interact with disease triggers to enhance disease expression or susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 40 publications
(39 reference statements)
3
35
0
2
Order By: Relevance
“…Pre-or post-natal exposure to high levels of MeHg causes mental retardation, cerebral palsy, seizures and ultimately death [66], while inorganic Hg is known to induce autoimmune disease in susceptible rodent strains. Additionally, in inbred strains of mice prone to autoimmune disease, Hg can accelerate and exacerbate disease manifestations [67]. Metals such as Hg may also contribute to the pathogenesis of autoimmune diseases by modulating mast cell activity [68].…”
Section: Mercurymentioning
confidence: 99%
“…Pre-or post-natal exposure to high levels of MeHg causes mental retardation, cerebral palsy, seizures and ultimately death [66], while inorganic Hg is known to induce autoimmune disease in susceptible rodent strains. Additionally, in inbred strains of mice prone to autoimmune disease, Hg can accelerate and exacerbate disease manifestations [67]. Metals such as Hg may also contribute to the pathogenesis of autoimmune diseases by modulating mast cell activity [68].…”
Section: Mercurymentioning
confidence: 99%
“…Thus, a 14-day pretreatment with HgCl 2 [two weeks of 20-200 µg mercury (kg body mass) -1 , subcutaneous, every second day] followed by an experimental induction of a lupus-like-disease, caused an increase in lupus-like symptoms in nonsusceptible mouse strains [72]. The authors concluded that mercury may act as a cofactor, which favors autoimmune disease when combined with other factors, such as genetic disposition or certain infectious disease [71].…”
Section: Autoimmunity In Nonsensitive Rodent Strainsmentioning
confidence: 99%
“…The first autoimmune responses were seen in rodents at a dose of about 50 µg mercury (kg body mass) -1 (day) -1 [72]. In a study with genetically mercury-susceptible mice, the threshold weekly dose for formation of antinuclear IgG was at 170 µg (kg body mass) -1 , or about 20 µg (kg body mass) -1 (day) -1 , for 10 weeks [40].…”
Section: Estimation Of Risk For Autoimmune Reactions In Humansmentioning
confidence: 99%
“…Silbergeld has found that mercury has a profound impact on graft versus host disease (GVHD) models of autoimmunity that mimic lupus (Via et al 2003). In these models, GVHD is induced by injecting splenocytes from one strain of mice (C57BL/6 or DBA/2) into hybrid offspring (C57BL/6 × DBA/2).…”
Section: The Environment and The Immune Systemmentioning
confidence: 99%